2006
DOI: 10.1093/pcp/pci252
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Induce Rapid Biosynthesis of Nitric Oxide (NO) in Arabidopsis thaliana Seedlings

Abstract: In this study, we examined the regulation by putrescine, spermidine and spermine of nitric oxide (NO) biosynthesis in Arabidopsis thaliana seedlings. Using a fluorimetric method employing the cell-impermeable NO-binding dye diaminorhodamine-4M (DAR-4M), we observed that the polyamines (PAs) spermidine and spermine greatly increased NO release in the seedlings, whereas arginine and putrescine had little or no effect. Spermine, the most active PA, stimulated NO release with no apparent lag phase. The response wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
266
0
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(302 citation statements)
references
References 68 publications
11
266
0
13
Order By: Relevance
“…Under these conditions, a NO-dependent increase in DAR-4M AM fluorescence (red color) was observed compared with the control seedlings (Fig. 5B), showing the specificity of this fluorescence probe in relation to NO, as previously reported for Arabidopsis wild type (Tun et al, 2006(Tun et al, , 2008. On the other hand, when the seedlings were preincubated with 200 mM 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO; a NO scavenger), the red fluorescence was greatly reduced (Fig.…”
Section: Localization Of No During the Development Of Arabidopsis Seesupporting
confidence: 87%
See 1 more Smart Citation
“…Under these conditions, a NO-dependent increase in DAR-4M AM fluorescence (red color) was observed compared with the control seedlings (Fig. 5B), showing the specificity of this fluorescence probe in relation to NO, as previously reported for Arabidopsis wild type (Tun et al, 2006(Tun et al, , 2008. On the other hand, when the seedlings were preincubated with 200 mM 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO; a NO scavenger), the red fluorescence was greatly reduced (Fig.…”
Section: Localization Of No During the Development Of Arabidopsis Seesupporting
confidence: 87%
“…The peroxisomes appeared in the form of spherical spots in all root tip cells. Figure 3B shows the same field analyzed using the diaminorhodamine-4M acetoxymethyl ester (DAR-4M AM) fluorescence probe, which also enabled NO to be detected (Kojima et al, 2001;Tun et al, 2006Tun et al, , 2008. An intense red fluorescence was found in spherical spots with a pattern similar to that of the GFP-PTS1.…”
Section: Localization Of No During the Development Of Arabidopsis Seementioning
confidence: 94%
“…As a small, highly diffusible gaseous molecule, NO functions as an intra-and intercellular messenger, inducing various processes including stress responses in plants. Rapid NO accumulation was reported after spermidine and spermine treatments without a lag phase, whereas putrescine had little effect in Arabidopsis [49]. In contrast, exogenous polyamines, especially putrescine, induced NO generation in soybean [50].…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 93%
“…Most work focuses on NOS-like enzyme (Gas et al 2009) and NR (Yamasaki and Sakihama 2000). Recent studies found that polyamine induced rapid biosynthesis of NO in Arabidopsis thaliana (Tun et al 2006;Yamasaki and Cohen 2006), suggesting there maybe a possible linkage between polyamine and nitric oxide. In our previous work, we found that NO scavenger cPTIO blocked the PAL activity increased by COS (Zhao et al 2007b), NO and H 2 O 2 induced by COS took part in inducing reduction in stomatal aperture and LEA protein gene expression in leaves of Brassica napus L. (Li et al 2009).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%